2015
DOI: 10.1186/s13071-014-0611-6
|View full text |Cite
|
Sign up to set email alerts
|

Theileria equi isolates vary in susceptibility to imidocarb dipropionate but demonstrate uniform in vitro susceptibility to a bumped kinase inhibitor

Abstract: BackgroundThe apicomplexan hemoparasite Theileria equi is a causative agent of equine piroplasmosis, eradicated from the United States in 1988. However, recent outbreaks have sparked renewed interest in treatment options for infected horses. Imidocarb dipropionate is the current drug of choice, however variation in clinical response to therapy has been observed.MethodsWe quantified the in vitro susceptibility of two T. equi isolates and a lab generated variant to both imidocarb dipropionate and a bumped kinase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 48 publications
1
35
0
1
Order By: Relevance
“…Imidocarb dipropionate, a dicationic diamidine of the carbanilide series of antiprotozoal compounds, has been effective against some of the T. equi strains causing infections in U.S. horses (Ueti, et al, 2012), making it the current drug of choice. However, variable responses to imidocarb treatment occur in both natural and experimental T. equi infection (Butler, et al, 2008, Frerichs, et al, 1973, Grause, et al, 2013, Knowles, 1996, Kumar, et al, 2003, Kumar, et al, 2009, Kuttler, et al, 1987, Ueti, et al, 2012), and we have recently documented treatment failure associated with in vitro imidocarb resistance (Hines, et al, 2015). Moreover, acute adverse effects are common due to the anticholinesterase activity of the drug (Tecles and Cerón, 2001).…”
Section: Inhibition Of Apicomplexan Parasite Growth and Replicatiomentioning
confidence: 88%
See 3 more Smart Citations
“…Imidocarb dipropionate, a dicationic diamidine of the carbanilide series of antiprotozoal compounds, has been effective against some of the T. equi strains causing infections in U.S. horses (Ueti, et al, 2012), making it the current drug of choice. However, variable responses to imidocarb treatment occur in both natural and experimental T. equi infection (Butler, et al, 2008, Frerichs, et al, 1973, Grause, et al, 2013, Knowles, 1996, Kumar, et al, 2003, Kumar, et al, 2009, Kuttler, et al, 1987, Ueti, et al, 2012), and we have recently documented treatment failure associated with in vitro imidocarb resistance (Hines, et al, 2015). Moreover, acute adverse effects are common due to the anticholinesterase activity of the drug (Tecles and Cerón, 2001).…”
Section: Inhibition Of Apicomplexan Parasite Growth and Replicatiomentioning
confidence: 88%
“…This selective difference in activity is sufficiently great to offer hope that further chemical elaboration, in particular of the R2 group, may allow distinguishing selectively between threonine-gatekeeper kinases of parasite and host. This extends the range of parasitic diseases potentially treatable with BKI drugs to include those caused by Plasmodium (Chapman, et al, 2013), Eimeria (Keyloun, et al, 2014), Theileria (Hines, et al, 2015), and Babesia (Pedroni, et al, 2016), all of which express threonine gatekeeper CDPKs. A validation of CDPK(s) as the sole molecular target(s) that cause inhibition of growth and proliferation of an apicomplexan parasite cells when exposed to BKIs will still need chemical genetic determination as demonstrated in T. gondii.…”
Section: Structural Basis Of Cross-parasite Cdpk Inhibition By Bkismentioning
confidence: 99%
See 2 more Smart Citations
“…By inhibiting certain highly conserved apicomplexan parasite CDPKs, bumped kinase inhibitors (BKIs) have shown broad ranging inhibitory effects in both in vitro and in vivo models of infections with Toxoplasma gondii , Cryptosporidium parvum , Plasmodium spp., Neospora caninum and Theileria equi (Murphy et al, 2010; Ojo et al, 2010, 2014a, b; Johnson et al, 2012; Castellanos-Gonzalez et al, 2013; Doggett et al, 2014; Hines et al, 2015; Huang et al, 2015; Vidadala et al, 2016). We have shown that inhibition of apicomplexan CDPK1 and subsequent interference with mammalian host cell invasion by BKIs was due to the atypical glycine “gatekeeper” residue in the ATP-binding site of the kinase as well as the overall topology of the ATP-binding site.…”
Section: Introductionmentioning
confidence: 99%